Studi empiris pengaruh kepuasan kerja, turnover intention, produktivitas, dan keunggulan bersaing - Eko Nur Fu'ad; Asep Gugun Gumilar (Jurnal Ekonomi dan Bisnis, 2018)
This study focused on CV Duta Jepara employees, a furniture company in Jepara Regency, to examine the effect of job satisfaction and turnover intention on productivity and competitive advantage of the company. This study processed primary data obtained using a questionnaire distributed to 468 employees. The research sample was selected using purposive sampling method with consideration of employees from the production department who had worked for more than two years. The samples analyzed were 275 questionnaires. The analytical tool used is Structural Equation Modeling. The results showed that job satisfaction affected turnover intention, productivity and competitive advantage. Turnover intention affects competitive advantage, but does not affect productivity. While productivity influences competitive advantage.